Building learning communities with character : how to integrate academic, social, and emotional learning - Novick, Bernard, 1933- (Association for Supervision and Curriculum Development, 2002)
Today's students need to learn more than just reading, writing, and arithmetic. They need to learn life skills to successfully manage tasks, form relationships, solve everyday problems, and adapt to the demands of simply growing up. To satisfy those needs, many educators seek effective and lasting programs for their students' academic, emotional, and social growth.